Decacarbonyl-1κ(3) C,2κ(3) C,3κ(4) C-bis[tris(3-chlorophenyl)phosphine]-1κP,2κP-triangulo-triruthenium(0) monohydrate - Shawkataly, Omar bin (International Union of Crystallography, 2010)
The asymmetric unit of the title triangulo-triruthenium compound, [Ru(3)(C(18)H(12)Cl(3)P)(2)(CO)(10)]·H(2)O, consists of one triangulo-triruthenium complex and one disordered water solvent molecule. Two of the 3-chlorophenyl rings are disordered over two positions with refined site occupancies of 0.671 (3)/0.329 (3) and 0.628 (3)/0.372 (3). The water molecule is disordered over two positions with refined site occupancies of 0.523 (7) and 0.477 (7). Two equatorial carbonyl groups have been substituted by the two monodentate phosphine ligands, leaving one equatorial and two axial carbonyl substituents on the two Ru atoms. The remaining Ru atom carries two equatorial and two axial terminal carbonyl ligands. In the crystal structure, molecules are linked into columns along the a axis by intermolecular C—H⋯Cl and C—H⋯O hydrogen bonds. The molecular structure is stabilized by weak intramolecular C—H⋯O hydrogen bonds.